2011
DOI: 10.1007/s13197-011-0559-x
|View full text |Cite
|
Sign up to set email alerts
|

Provitamin A carotenoids in biofortified maize and their retention during processing and preparation of South African maize foods

Abstract: Provitamin A-biofortified maize may contribute to alleviating vitamin A deficiency (VAD), in developing countries. However, processing the maize into food products may reduce its provitamin A content. The aims of this study were to determine the composition of provitamin A carotenoids in biofortified maize varieties as well as to assess their retention during processing of popular maize foods consumed in KwaZulu-Natal, South Africa. The non-provitamin A carotenoid, zeaxanthin and the provitamin A carotenoids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 21 publications
5
53
3
3
Order By: Relevance
“…Most of the carotenoids were retained during this process except for β-cryptoxanthin, which showed a consistent 60% retention across all genotypes (Table 3). These findings were contrary to those reported by Pillay et al, 9 where a higher retention of β-cryptoxanthin (95.3−113.5%) was observed in milled maize. Different maize genotypes and milling processes could be a source of variation with reported studies.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
“…Most of the carotenoids were retained during this process except for β-cryptoxanthin, which showed a consistent 60% retention across all genotypes (Table 3). These findings were contrary to those reported by Pillay et al, 9 where a higher retention of β-cryptoxanthin (95.3−113.5%) was observed in milled maize. Different maize genotypes and milling processes could be a source of variation with reported studies.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
“…For cooked products, the retention varies depending on the type of cooking. For traditional cooked dough (Phutu) the retention of provitamin A carotenoids was between 107 and 118% as found by Pillay et al [21]. Fried products generally presented a higher degree of degradation, whereas boiled products presented better retention.…”
Section: Maizementioning
confidence: 79%
“…During both milling and processing, biofortified maize hybrids showed good levels of retention of provitamin A carotenoids when using apparent retention values [21]. The retention values were measured between 105 and 137% in maize meal and samp, respectively.…”
Section: Maizementioning
confidence: 99%
“…Some of the promising lines had high provitamin A content by accumulating mainly higher levels of b-carotene at the expense of the synthesis of other carotenoids while others contained high provitamin A by accumulating high levels of both carotenes and xanthophylls. These lines will be useful not only for the development of hybrids and synthetics with high concentration of carotens and xanthopylls but also for elucidating the mechanisms that regulate the synthesis of more substrates upstream in the carotenoid biosynthetic pathway and the resulting increased flux downstream Table 3 Provitamin A contenet and grain yields of the best five synthetic varieties (OPV) and hybrids selected from each of the two regional trials evaluated at four to six locations in 2013, 2014 and 2015 Even though significant progress has been made in boosting provitamin A to higher levels in tropical maize, studies have demonstrated that the loss in provitamin A during storage, milling, and preparation of diverse traditional foods may reach up to 70% (Muzhingi et al 2008;Mugode et al 2014;Pillay et al 2014;De Moura et al 2015). Also, the extent of loss in provitamin A carotenoids exhibits a broad range of variation among maize genotypes in these studies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%